Advantages of Modified Computed Tomography Severity Index of Acute Pancreatitis Over Other Scoring System - Sharif, Md Mofazzal; Rekha, Khaleda Parvin; Siddiqua, Umme Iffat; Khatun, Mst Monira; Haque, AKM Enamul; Arifin, Saiful (KYAMC Journal, 2019)
Pancreatitis is one of most complex and clinically challenging of all abdominal disorders. USG and abdominal Computed Tomography (CT) are the most commonly used diagnostic imaging modalities for the evaluation of pancreas. Computed Tomography (CT) is highly accurate and sensitive than USG in both diagnosing as well as demonstrating the extent. Early assessment of the cause and severity of acute pancreatitis is of utmost importance for prompt treatment and close monitoring of patient with severe disease. CT is the imaging method of choice for assessing the extent of acute pancreatitis and for evaluating complications. CT severity index is used to assess prognostic correlation and clinical outcome of acute pancreatitis. Modified CT severity index makes the score easier to calculate and reduces the inter-observer variation. KYAMC Journal Vol. 10, No.-2, July 2019, Page 110-113